Targeting DDX3 with a small molecule inhibitor for lung cancer therapy - Bol, Guus M (EMBO Mol Med, 2015)
Lung cancer is the most common malignancy worldwide and is a focus for developing targeted therapies due to its refractory nature to current treatment. We identified a RNA helicase, DDX3, which is overexpressed in many cancer types including lung cancer and is associated with lower survival in lung cancer patients. We designed a first-in-class small molecule inhibitor, RK-33, which binds to DDX3 and abrogates its activity. Inhibition of DDX3 by RK-33 caused G1 cell cycle arrest, induced apoptosis, and promoted radiation sensitization in DDX3-overexpressing cells. Importantly, RK-33 in combination with radiation induced tumor regression in multiple mouse models of lung cancer. Mechanistically, loss of DDX3 function either by shRNA or by RK-33 impaired Wnt signaling through disruption of the DDX3–β-catenin axis and inhibited non-homologous end joining—the major DNA repair pathway in mammalian somatic cells. Overall, inhibition of DDX3 by RK-33 promotes tumor regression, thus providing a compelling argument to develop DDX3 inhibitors for lung cancer therapy.